Inter- and Intra-Observer Variability of the Volume of Cervical Ossification of the Posterior Longitudinal Ligament Using Medical Image Processing Software - Shin, Dong Ah (J Korean Neurosurg Soc, 2017)
OBJECTIVE: Computed tomography (CT)-based method of three dimensional (3D) analysis (MIMICS(®), Materialise, Leuven, Belgium) is reported as very useful software for evaluation of OPLL, but its reliability and reproducibility are obscure. This study was conducted to evaluate the accuracy of MIMICS(®) system, and inter- and intra-observer reliability in the measurement of OPLL. METHODS: Three neurosurgeons independently analyzed the randomly selected 10 OPLL cases with medical image processing software (MIMICS(®)) which create 3D model with Digital Imaging and Communication in Medicine (DICOM) data from CT images after brief explanation was given to examiners before the image construction steps. To assess the reliability of inter- and intra-examiner intraclass correlation coefficient (ICC), 3 examiners measured 4 parameters (volume, length, width, and length) in 10 cases 2 times with 1-week interval. RESULTS: The inter-examiner ICCs among 3 examiners were 0.996 (95% confidence interval [CI], 0.987–0.999) for volume measurement, 0.973 (95% CI, 0.907–0.978) for thickness, 0.969 (95% CI, 0.895–0.993) for width, and 0.995 (95% CI, 0.983–0.999) for length. The intra-examiner ICCs were 0.994 (range, 0.991–0.996) for volume, 0.996 (range, 0.944–0.998) for length, 0.930 (range, 0.873–0.947) for width, and 0.987 (range, 0.985–0.995) for length. CONCLUSION: The medical image processing software (MIMICS(®)) provided detailed quantification OPLL volume with minimal error of inter- and intra-observer reliability in the measurement of OPLL.